A NEW INVESTIGATION OF VIETNAM’S BERYL - Nguyen Van Binh; Nguyen Thi Hong (ASEAN Journal on Science and Technology for Development, 2008)
The paper presents briefly new investigation of Vietnam beryl group, especially some characteristics of regional geology of Song Chay granite massif and new find of big crystals of beryl in them. The green beryl is found in quartz - mica - tourmaline, mica - feldspar – quartz pegmatite bodies in the south part of Song Chay granite - gneiss massif near Na Chi and Tan Nam villages, Quang Binh district, Ha Giang province.